Pembuatan MOCAF (Modified Cassava Flour) Sebagai Upaya Optimalisasi Pemanfaatan Singkong Pada Masyarakat Di Kelurahan Geres, Lombok Timur - Satrijo Saloko; Wiryasri Wiryasri; Virnia Wanda Utami; Rizky Annisa Ramadhini; Baiq Desi Nurma Sari; Devi Apresia Monica; Hafifah Indar Parawangsa; Mediana Mediana; Wahyu Alfandi; Yuliana Yuliana; Yusril Hadi (Jurnal Gema Ngabdi, 2022)
Cassava is one of the biggest commodities produced by the people of Geres (East Lombok). The high yield of cassava is not matched by the lack of utilization, so the selling value in the market is subordinate. The effort needed to enhance the selling value of cassava in the market is by making MOCAF. MOCAF is modified cassava flour with the principle of modifying cassava cells by fermentation. Regarding the development of the MOCAF business which rare and has great potential, so that the KKN Geres 2021/2022 with the theme of using cassava as MOCAF to support food diversity in Geres Village and expand the selling power of cassava. The purpose of the first activity is providing an explanation concerning MOCAF which is expected to increase public understanding due to the processing of cassava into MOCAF. The second activity is through direct training on the manufacture and packaging of MOCAF with the local community. The results of the activity are upgrading community knowledge and skills in processing cassava into MOCAF, as well as media like pamphlet to guide for making MOCAF.